PELAKSANAAN POLA PEMURIDAN KAMBIUM DALAM MEMBERIKAN DASAR KEYAKINAN KESELAMATAN ANAK USIA 13 – 18 TAHUN - Frets Keriapy (Bethel Press, 2021)
Discipleship is a Christian’s duty, whoever he is. This is a must for disciples of Jesus. Before He ascended to Heaven, He gave the final message to His disciple to do discipleship to all nations. In this research, the discipleship process used was KAMBIUM pattern. KAMBIUM is a pattern of discipleship used by PESAT North Maluku in making disciples. The method used in this scientific paper is to use qualitative methods with data collection using interviews and observations. The results of this research indicate that the KAMBIUM pattern discipleship process has a significant impact on beliefing in salvation in God for children aged 13-18 years.